Unveiling chlorpyrifos mineralizing and tomato plant-growth activities of Enterobacter sp. strain HSTU-ASh6 using biochemical tests, field experiments, genomics, and in silico analyses - Haque, Md. Azizul; Hossain, Md. Shohorab; Ahmad, Iqrar; Akbor, Md. Ahedul; Rahman, Aminur; Manir, Md. Serajum; Patel, Harun M.; Cho, Kye Man (Frontiers in Microbiology, 2022)
The chlorpyrifos-mineralizing rice root endophyte Enterobacter sp. HSTU-ASh6 strain was identified, which enormously enhanced the growth of tomato plant under epiphytic conditions. The strain solubilizes phosphate and grew in nitrogen-free Jensen’s medium. It secreted indole acetic acid (IAA; 4.8 mg/mL) and ACC deaminase (0.0076 µg/mL/h) and hydrolyzed chlorpyrifos phosphodiester bonds into 3,5,6-trichloro-2-pyridinol and diethyl methyl-monophosphate, which was confirmed by GC–MS/MS analysis. In vitro and in silico (ANI, DDH, housekeeping genes and whole genome phylogenetic tree, and genome comparison) analyses confirmed that the strain belonged to a new species of Enterobacter. The annotated genome of strain HSTU-ASh6 revealed a sets of nitrogen-fixing, siderophore, acdS, and IAA producing, stress tolerance, phosphate metabolizing, and pesticide-degrading genes. The 3D structure of 28 potential model proteins that can degrade pesticides was validated, and virtual screening using 105 different pesticides revealed that the proteins exhibit strong catalytic interaction with organophosphorus pesticides. Selected docked complexes such as α/β hydrolase–crotoxyphos, carboxylesterase–coumaphos, α/β hydrolase–cypermethrin, α/β hydrolase–diazinon, and amidohydrolase–chlorpyrifos meet their catalytic triads in visualization, which showed stability in molecular dynamics simulation up to 100 ns. The foliar application of Enterobacter sp. strain HSTU-ASh6 on tomato plants significantly improved their growth and development at vegetative and reproductive stages in fields, resulting in fresh weight and dry weight was 1.8–2.0-fold and 1.3–1.6-fold higher in where urea application was cut by 70%, respectively. Therefore, the newly discovered chlorpyrifos-degrading species Enterobacter sp. HSTU-ASh6 could be used as a smart biofertilizer component for sustainable tomato cultivation.